Methods of optimization of distributed databases in oracle – part 2 - Barczak, Andrzej; Zacharczuk, Dariusz; Pluta, Damian (Studia Informatica. System and information technology, 2019)
The second part of the paper devoted to optimization of distributed databases. This part presents tests which confirm the efficiency of database tuning methods, described in part one. Analysis of tests results based on the developed database is presented.